Analysis of Critical Thinking Skills in Vocational High School Automotive Engineering Students (Universitas Negeri Semarang, 2020)
The 21st Century demands that every human being be able to solve the problems faced by thinking creatively and critically and be able to use information and communication technology wisely. The business world and industry needs workers who have the ability of the 21st century so that market needs can be met. Vocational Schools are educational institutions that are expected to produce graduates who are ready to work and can compete in the business world and the industry. Supposedly, the implementation of learning in SMK is oriented to the reality of future work needs. This study uses descriptive qualitative methods and aims to analyze the findings related to the level of critical thinking skills of vocational students, especially automotive engineering expertise programs, the factors that influence, and the steps that can be taken to improve students' critical thinking skills. The results showed that as much as 58.34% had a level of critical thinking skills that were lacking, even 5.56% of them were classified as very less. Some previous research states that the factors that influence critical thinking skills of vocational students are classified as low, namely student input, quality of learning, and support in learning. Actions that can be taken to improve students' critical thinking skills include improving teaching methods or models, familiarizing students with questions that demand critical thinking, and using teaching materials that support critical thinking skills.